Clinical frailty and functional trajectories in hospitalized older adults: A retrospective observational study. Issue 7 (18th July 2016) - Hartley, Peter; Adamson, Jennifer; Cunningham, Carol; Embleton, Georgina; Romero‐Ortuno, Roman
Abstract : Aim: Frailty predicts inpatient mortality and length of stay, but its link to functional trajectories is under‐researched. Addenbrooke's Hospital, Cambridge, UK, collects the Clinical Frailty Scale (CFS) within 72 h of admission for those aged ≥75 years. We studied whether the CFS links to functional trajectories in hospitalized older adults. Methods: This was a retrospective observational study in an English university hospital. We analyzed all first episodes of county residents aged ≥75 years admitted to the Department of Medicine for the Elderly wards between December 2014 and May 2015. Data were extracted from the hospital's information systems. Patients were classified as non‐frail (CFS 1–4), moderately frail (CFS 5–6) and severely frail (CFS 7–8). Function was retrospectively measured with the modified Rankin Scale (mRS) at preadmission, admission and discharge. Results: Of 539 eligible patients, 46 died during admission (mortality rates: 2% in CFS 1–4, 5% in CFS 5–6, 19% in CFS 7–8). Among the 493 survivors, 121 were non‐frail, 235 moderately and 137 severely frail. The mean mRS of the non‐frail was 1.8 (95% CI 1.7–2.0) at baseline, 3.3 (95% CI 3.1–3.5) on admission and 2.2 (95% CI 2.0–2.3) on discharge (mean length of stay 9 days). The moderately frail had a mean mRS of 2.9 (95% CI 2.8–3.0) at baseline, 4.0 (95% CI 3.8–4.1) on admission and 3.2 (95% CI 3.1–3.3) on discharge (mean length of stay 15 days). The severely frail had mean mRS of 3.5 (95% CI 3.3–3.6) at baseline, 4.3 (95% CI 4.1–4.4) on admission and 3.7 (95% CI 3.6–3.9) on discharge, respectively (mean length of stay 17 days). Conclusions: In older inpatients, frailty might be linked to lower and slower functional recovery. Prospective work is required to confirm these trajectories and understand how to influence them.Geriatr Gerontol Int 2017; 17: 1063–1068.